Dynamics of contraceptive use among young women in Nepal - Kafle, Ramesh Babu (Nepal Population Journal, 2018)
This paper examines the dynamics of contraceptive use of currently married young women (age 15-24) in Nepal by analyzing the trends and differentials in contraceptive use, the changes in method mix and the determinants of contraceptive use by selected socioeconomic and demographic characteristics. The reasons of non-use of contraception are also assessed. Data from the three rounds of nationally representative Nepal Demographic and Health Survey (NDHS) 2001, 2006 and 2011 are used. Currently married women aged 15-24 are selected and included in analysis. Study sample constitute 2573, 2398 and 2552 eligible women in NDHS 2001, 2006 and 2011 respectively. Use of contraception among young couples is gradually increasing in almost all subgroups of population in Nepal, with narrowing differentials by education and economic condition of household. Tendency of starting contraceptives before having a child is also emerging. There is declining share of sterilization among youth indicating either a probable shifting in age at sterilization or more favour towards temporary methods. Injection has the highest share in all the three surveys. The share of long acting temporary methods (IUD and Implants) is quite small and almost same in all the three surveys. Couples still feel safe to start using contraceptives after having at least one son however, the differences are declining. Reasons for non-use like fear of side effects and opposition to use are sharply declining over time but that due to husband’s absence is emerging as almost a sufficient reason for non-use of contraception among young married women in Nepal. The family planning program should focus on meeting the family planning needs of young couples of all strata of population with special thrust on those women whose husbands are currently in foreign country so that they would be able to avoid unintended pregnancy on their husband’s come back.